How to evaluate adolescents’ dental anxiety? A review of instruments - Nascimento, Michele; Murielly, Trícia; Assis, Patrícia; Maciel, Carolina; Colares, Viviane (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Introduction: The prevalence of dental anxiety appears to be relatively consistent throughout the world, but some studies reports higher levels than others. This may be related to different instruments used. Objective: to identify and describe the main instruments used in the assessment of dental anxiety in adolescents. Material and Methods: Literature review. Original studies involving adolescents, in which the methodology comprised the application of some instrument to identify and / or quantify the phenomenon, were included. The search was limited to English, Portuguese and Spanish publications in the period between 2012 and 2016. Reviews, Meta-analyzes and case reports were excluded. The selected databases were MEDLINE (via PubMed) and LILACS (via BVS); and the search was developed with the following descriptors: ’dental anxiety’, ’adolescents’, ’Surveys and Questionnaires’ (MeSH), combined by the Boolean operator AND. Results: Ten psychometric instruments are available to assess dental anxiety. The most frequently used instrument is the Dental Anxiety Scale (DAS), presented in nine studies. Less frequently used is the Facial Image Scale (FIS), presented in only one investigation. Most of the instruments affords translations into other languages, including Portuguese. Conclusion: The most used instrument is the DAS, followed by its modified version, the MDAS. Usually, more than one instrument has been used to correlate the findings and to provide the measured construct a greater consistency. Descriptors: Dental Anxiety; Adolescent; Surveys and Questionnaires. References Stenebrand A, Wide Boman U, Hakeberg M. Dental anxiety and symptoms of general anxiety and depression in 15‐year‐olds. Int J Dent Hyg. 2013; 11(2):99-104. American Psychiatric Association. DSM-5: Manual diagnóstico e estatístico de transtornos mentais. São Paulo:Artmed; 2014. Folayan MO, Idehen EE, Ojo OO. The modulating effect of culture on the expression of dental anxiety in children: a literature review. Int J Paediatr Dent. 2014;14(4):241-45. Hathiwala S, Acharya S, Patil S. Personality and psychological factors: Effects on dental beliefs. J Indian Soc Pedod Prev Dent. 2015;33(2):88-92. Jaakkola S, Lahti S, Räihä H, Saarinen M, Tolvanen M, Aroma et al. Dental fear affects adolescent perception of interaction with dental staff. Eur J Oral Sci. 2014;122(5):339-45. Murthy AK, Pramila M, Ranganath, S. Prevalence of clinical consequences of untreated dental caries and its relation to dental fear among 12–15-year-old schoolchildren in Bangalore city, India. Eur Arch Paediatr Dent. 2014;15(1):45-9. Lundgren GP, Karsten A, Dahllöf G. Oral health-related quality of life before and after crown therapy in young patients with amelogenesis imperfecta. Health Qual Life Outcomes. 2015;13:197 Hollis A, Willcoxson F, Smith A, Balmer R. An investigation into dental anxiety amongst paediatric cardiology. patients. Int J Paediatr Dent. 2015;25(3):183-90. Viswanath D, Krishna AV. Correlation between dental anxiety, sense of coherence (SOC) and dental caries in school children from Bangalore North: A cross-sectional study. J Indian Soc of Pedod Prev Dent. 2015; 33:15-8. Soares FC, Souto G, Lofrano M, Colares V. Anxiety related to dental care in children and adolescents in a low-income Brazilian community. Eur Arch Paediatr Dent. 2015;16(2): 149-52. Moher D, Liberati A, Tetzlaff J, Altman DG, Prisma Group. Preferred reporting items for systematic reviews and meta-analyses: the PRISMA statement. PLoS Medicine. 2009;6(7):e1000097. Costa A, Terra JO, de Souza SMP, de Souza Terra F, Elias G, Freire R. Ansiedade ao tratamento odontológico em escolares do ensino médio no município de Alfenas-MG. Periodontia. 2014;24(2):13-8. Crego A, Carrillo‐Diaz M, Armfield J M, Romero M. Dental fear and expected effectiveness of destructive coping as predictors of children’s uncooperative intentions in dental settings. Int J Paediatr Dent. 2015;25(3):191-98. Houtem CMHH, Wijk AJ, Boomsma DI, Ligthart L, Visscher CM, Jongh, A. Self-reported gagging in dentistry: prevalence, psycho-social correlates and oral health. J Oral Rehabil. 2015;42(7):487-94. Muppa R, Bhupatiraju P, Duddu M, Penumatsa NV, Dandempally A, Panthula P. Comparison of anxiety levels associated with noise in the dental clinic among children of age group 6-15 years. Noise Health. 2013;15(64):190-3. Östberg AL, Abrahamsson KH. Oral health locus of control in a Swedish adolescent population. Acta Odontol Scand. 2013;71(1):249-55. Patel H, Reid C, Wilson K, Girdler NM. Inter-rater agreement between children’s self-reported and parents’ proxy-reported dental anxiety. Br Dent J. 2015;218(4):E6. Taskinen H, Kankaala T, Rajavaara P, Pesonen P, Laitala ML, Anttonen V. Self-reported causes for referral to dental treatment under general anaesthesia (DGA): a cross-sectional survey. Eur Arch Paediatr Dent. 2014;15(2):10512. Viinikangas A, Lahti S, Yuan Pietilä I, Freeman R, Humphris G. Evaluating a single dental anxiety question in Finnish adults. Acta Odontol Scand. 2007;65(4):236-40. Carrillo-Diaz M, Crego A, Romero-Maroto M. The influence of gender on the relationship between dental anxiety and oral health-related emotional well-being. Int J Paediatr Dent. 2013;23(3):180-87. Crego A, Carrillo-Diaz M, Armfield JM, Romero M. Applying the Cognitive Vulnerability Model to the analysis of cognitive and family influences on children’s dental fear. Eur J Oral Sci. 2013;121(3pt1):194-203. Marya CM, Grover S, Jnaneshwar A, Pruthi N. Dental anxiety among patients visiting a dental institute in Faridabad, India. West Indian Med J. 2012;61(2):187-90. Wiener RC. Dental fear and delayed dental care in Appalachia-West Virginia. J Dent Hyg. 2015; 89(4):274-81. Esa R, Ong AL, Humphris G, Freeman R. The relationship of dental caries and dental fear in Malaysian adolescents: a latent variable approach. BMC Oral Health. 2014;14:19. Stenebrand A, Wide Boman U, Hakeberg M. General fearfulness, attitudes to dental care, and dental anxiety in adolescents. Eur J Oral Sci. 2013;121(3pt2):252-57. Worsley DJ, Marshman Z, Robinson PG, Jones K. Evaluation of the telephone and clinical NHS urgent dental service in Sheffield. Community Dent Health. 2016;33(1):9-14. Majstorovic M, Morse DE, Do D, Lim LL, Herman NG, Moursi AM. Indicators of dental anxiety in children just prior to treatment. J Clin Pediatr Dent. 2014;39(1):12-7. Rantavuori K, Tolvanen M, Lahti S. Confirming the factor structure of modified CFSS-DS in Finnish children at different ages. Acta Odontol Scand.2012;70(5):421-25. Armfield JM. What goes around comes around: revisiting the hypothesized vicious cycle of dental fear and avoidance. Community Dent Oral Epidemiol. 2013;41(3):279-87. Carrillo-Diaz M, Crego A, Armfield JM, Romero M. Dental fear-related cognitive vulnerability perceptions, dental prevention beliefs, dental visiting, and caries: a cross-sectional study in Madrid (Spain). Community Dent Oral Epidemiol. 2015;43(4):375-84. Ferreira AMB, Colares V. Validation of the Brazilian Version of the Fear of Dental Pain Questionnaire-Short Form (S-FDPQ). Pesq Bras Odontoped Clin Integr. 2011;11(2):275-79. Toscano MA, Zacharczuk G, López GE, García MA. Ansiedad de los niños frente a la consulta odontológica: prevalencia y factores relacionados. Bol AAON. 2012;21(3):9-13. Corah NL. Development of a dental anxiety scale J Dent Res. 1969;48(4):596. Humphris GM, Dyer TA, Robinson PG. The modified dental anxiety scale: UK general public population norms in 2008 with further psychometrics and effects of age. BMC Oral Health. 2009;9:20. Howard KE, Freeman R. Reliability and validity of a faces version of the Modified Child Dental Anxiety Scale. Int J Paediatr Dent. 2007; 17(4):281-88. Kleinknecht RA, Klepac RK, Alexander LD. Origins and characteristics of fear of dentistry. J Am Dent Assoc. 1973;86(4):842-48. Schuurs AHB, Hoogstraten J. Appraisal of dental anxiety and fear questionnaires; a review. Community Dent Oral Epidemiol.1993; 21(6):329-39. Oliveira MA, Bendo CB, Paiva SM, Vale M, Serra-Negra JM. Determining cut-off points for the dental fear survey. ScientificWorldJournal. 2015;2015:983564 Marginean I, Filimon L. Dental Fear Survey: a validation study on the Romanian population. JPER. 2011;19(2):124-38. Neverlien PO. Assessment of a single-item dental anxiety question. Acta Odontol Scand. 1990;48(6):365-69. Cuthbert MI, Melamed BG. A screening device: Children at risk for dental fear and management problems. ASDC J Dent Child. 1982;49(6):432–36 El-Housseiny AA, Farsi, NM, Alamoudi NM, Bagher SM, El Derwi D. Assessment for the Children’s Fear Survey Schedule—Dental Subscale. J Clin Pediatr Dent. 2014;39(1):40-46. Rantavuori K, Tolvanen M, Lahti S. Confirming the factor structure of modified CFSS-DS in Finnish children at different ages. Acta Odontol Scand. 2012;70(5):421-25. Armfield JM. Australian population norms for the Index of Dental Anxiety and Fear (IDAF‐4C). Aust Dent J. 2011;56(1):16-22. Armfield JM. Development and psychometric evaluation of the Index of Dental Anxiety and Fear (IDAF-4C+). Psychol Assess. 2010;22(2):279-87. Buchanan H, Niven N. Validation of a Facial Image Scale to assess child dental anxiety. Int J Paediatr Dent. 2002;12(1):47-52. Kilinç G, Akay A, Eden E, Sevinç N, Ellidokuz H. Evaluation of children’s dental anxiety levels at a kindergarten and at a dental clinic. Braz Oral Res.2016;30(1):e-72. Abanto J, Vidigal EA, Carvalho TS, Bönecker M. Factors for determining dental anxiety in preschool children with severe dental caries. Braz oral res. 2017;31:e-13. Armfield JM. How do we measure dental anxiety and fear and what are we measuring anyway? Oral Health Prev Dent. 2010;8(1):107-15.